PROBLEMATIKA SISWA DALAM PEMBELAJARAN BAHASA ARAB SERTA UPAYA DALAM MENANGGULANGINYA - Nurtresnaningsih, Ineu (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2018)
The background of this research problem, among others, clearly visible differences in the ability of learning Arabic in the same class even though the material provided in accordance with the student's academic level. This study used a qualitative approach that seeks to describe actual realities on the ground. Data collection methods used include, library research, observation, interviews, and documentation. Field was discovered that 1) there are things that Affect several differences in ability levels of students in learning Arabic in the same class, 2) some of the solutions that can be used to overcome reviews these problems. The conclusion that each individual is different in some respects, particularly in learning Arabic and learning methods by teachers varied greatly affect in tackling these problems. Individual differences among students who appeared in learning Arabic as a second language are: age, sex, closeness between the first language learners and the Arabic language, mastery of the first language learners, Personal factors, the tendency of language, attitude towards Arabic and culture, motivation to learn Arabic, learning styles and so forth.